2018
DOI: 10.1002/ca.23214
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Cycling Power and Muscle Thickness in Cyclists

Abstract: The aim of this study was to determine the correlation between muscle thickness (MT) and cycling power in varsity cyclists using ultrasonography (US) and to identify any differences in MT between short- and long-distance cyclists. Twelve cyclists participated in this study. Real-time two-dimensional B-mode US was used to measure the MT in the anterior thigh, anterior lower leg, and trunk, especially in the abdominal and lumbar regions. A cycle ergometer was used to measure cycling power parameters such as maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 20 publications
2
19
1
Order By: Relevance
“…These different architectural characteristics of the muscle are associated with faster sprint performances. Lee et al also demonstrated that the muscles in the anterior thigh and abdominal regions were thicker in short-distance cyclists than in long-distance cyclists 1 . These differences in muscle architecture could be attributed to short-distance cyclists generating larger forces over shorter times and shorter distances compared to long-distance cyclists, and resulted in the 20-s cycling power being higher in short-distance cyclists in the present study.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…These different architectural characteristics of the muscle are associated with faster sprint performances. Lee et al also demonstrated that the muscles in the anterior thigh and abdominal regions were thicker in short-distance cyclists than in long-distance cyclists 1 . These differences in muscle architecture could be attributed to short-distance cyclists generating larger forces over shorter times and shorter distances compared to long-distance cyclists, and resulted in the 20-s cycling power being higher in short-distance cyclists in the present study.…”
Section: Discussionmentioning
confidence: 96%
“…Those authors found that the VL and VM muscle thicknesses were significantly correlated with the 5-s and 30-s cycling powers. In addition, the thickness of the VL predicted the 5-s and 30-s cycling powers in a stepwise multiple regression analysis 1 . Ericson reported that that knee extensor contributed 39% of the cycling power 5,21 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The muscle is a crucial structure in the human body because it is used in all movements, from simple to detailed movements such as standing, sitting, and walking. Previous studies have shown that muscle thickness is proportional to muscle power [16]. However, as the age increases, the muscle volume decreases, leading to muscle weakening.…”
Section: Discussionmentioning
confidence: 95%
“…The larger the FA, the higher the capacity to pack the contractile material into a certain volume, thus producing strength [14][15][16]. Muscles are classi ed according to their shape, and it is known that the pennate muscle can have more muscle bers per unit area than other kinds of muscle, thereby having the ability to generate large force by providing a larger physiological cross-section [12,17,18]. These muscle development characteristics directly affect the force production and can manifest differently, depending on the sports category [19].…”
Section: Introductionmentioning
confidence: 99%